Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1152/japplphysiol.00378.2013
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of regional fractional ventilation in human subjects by measurement of hyperpolarized3He washout with 2D and 3D MRI

Abstract: Multiple-breath washout hyperpolarized (3)He MRI was used to calculate regional parametric images of fractional ventilation (r) as the ratio of fresh gas entering a volume unit to the total end inspiratory volume of the unit. Using a single dose of inhaled hyperpolarized gas and a total acquisition time of under 1 min, gas washout was measured by dynamic acquisitions during successive breaths with a fixed delay. A two-dimensional (2D) imaging protocol was investigated in four healthy subjects in the supine pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 38 publications
5
92
0
Order By: Relevance
“…Emami et al (10) reduced the use of gas and the duration of the protocol by implementing a wash-in ventilation sequence in pigs whereby an image was obtained after each breath over the multibreath sequence. Recently, Horn et al (11) performed multibreath 3 He ventilation imaging in human subjects by using a washout technique. However, as washout of the polarized gas proceeded, the signal-tonoise ratio often decreased such that only the images obtained after the first two or three breaths of the protocol were usable.…”
Section: Definition Of Fractional Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Emami et al (10) reduced the use of gas and the duration of the protocol by implementing a wash-in ventilation sequence in pigs whereby an image was obtained after each breath over the multibreath sequence. Recently, Horn et al (11) performed multibreath 3 He ventilation imaging in human subjects by using a washout technique. However, as washout of the polarized gas proceeded, the signal-tonoise ratio often decreased such that only the images obtained after the first two or three breaths of the protocol were usable.…”
Section: Definition Of Fractional Ventilationmentioning
confidence: 99%
“…Without this adjustment of Pao 2 values, fractional ventilation would have been overestimated by approximately 10%. This approach thus builds on that of Horn et al (11), whose washout technique did not provide enough signal to directly produce a high-spatialresolution regional Pao 2 map.…”
Section: Technical Developments: Regional Fractional Ventilation Measmentioning
confidence: 99%
“…Following this, hyperpolarized helium-3 MRI (HP 3 He MRI) has been examined in multiple settings and has shown high sensitivity for the detection of ventilation impairments [34][35][36][37][38][39][40][41][42][43][44]. This typically requires production of hyperpolarized gas on site which is then mixed with nitrogen and administered to patients with a one litre Tedlar Bag.…”
Section: Hyperpolarized Helium-3 Mrimentioning
confidence: 99%
“…Nevertheless, the method requires further testing and adjustments and only one CF patient was tested to check the tolerability of the protocol (Fig. 1) [44]. Hyperpolarized xenon-129 MRI 3 He is difficult and expensive to obtain due to the increasing demand for the helium-3 isotope in non-MRI applications and it is typically only sourced from the tritium decay in nuclear warheads [45] making the development of an alternative HP MRI noble gas highly desirable.…”
Section: Hyperpolarized Helium-3 Mrimentioning
confidence: 99%
“…Recently published data of YSERBYT et al [60] on pulmonary confocal laser endomicroscopy of distal airways confirmed that this is a promising new technique for the in vivo evaluation of the respiratory tract and the three-dimensional characteristics of the pulmonary acinus. HORN et al [61] used hyperpolarised 3 He gas ventilation magnetic resonance imaging (MRI) to map bronchodilator treatment response in COPD. This concept is able to regionally resolve changes in lung ventilation in response to therapy in COPD [62].…”
Section: Morphological and Functional Imagingmentioning
confidence: 99%